2010
DOI: 10.1002/ibd.21331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corticosteroid dose and duration of administration on colonic anastomosis

Abstract: High and low doses of the corticosteroid produced adverse effects on the healing of colon anastomosis in rats regardless of whether it was administered over a long or short preoperative period. However, the most prominent negative effect was associated with high-dose, long-term corticosteroid administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…Although corticosteroids are generally thought to impair intestinal anastomotic healing, this effect has never been proven unequivocally in clinical studies . Some experimental studies have concluded that corticosteroid use impairs the healing of colonic anastomosis in a rat model , but others have reported no such effect . Baca et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although corticosteroids are generally thought to impair intestinal anastomotic healing, this effect has never been proven unequivocally in clinical studies . Some experimental studies have concluded that corticosteroid use impairs the healing of colonic anastomosis in a rat model , but others have reported no such effect . Baca et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although corticosteroids are generally thought to impair intestinal anastomotic healing, this effect has never been proven unequivocally in clinical studies [20]. Some experimental studies have concluded that corticosteroid use impairs the healing of colonic anastomosis in a rat model [21][22][23], but others have reported no such effect [20]. Baca et al [23] conducted an experimental study to investigate how long-and short-term corticosteroid administration in high and low doses modulated the course of the healing process for colonic anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Not surprisingly, long-term administration of high-dose steroids has been shown to cause the most impairment in healing. 40 In systemic analysis, steroids have been shown to increase anastomotic leak rate. 41 Muddying the waters a bit is a study on patients with inflammatory bowel disease, which demonstrated no increase in anastomotic leak in patients who are on low-and high-dose steroids at the time of surgery.…”
Section: Steroids/immune Modulatorsmentioning
confidence: 99%
“…Despite the beneficial anti‐inflammatory effects of corticosteroids, there are potential negative effects on corneal healing, which frequently preclude their use in equine ulcerative keratitis. Corticosteroids have been associated with a delayed repair in several nonocular tissues . Specific to ophthalmology, corticosteroids have been found to retard corneal epithelial defect closure and contribute to lower corneal stromal cell density in a dose‐dependent manner .…”
Section: Introductionmentioning
confidence: 99%